Introduction to the Special Issue 2025 Looking Back and Looking Ahead: A Wide Angle Lens on Audiovisual Translation - Chiaro, Delia; Rossato, Linda (Journal of Audiovisual Translation, 2025)
This special issue provides a diachronic, critical examination of the accelerating challenges and transformations facing audiovisual translation (AVT)’s practice and research due to constant technological innovation. By tracing AVT's historical evolution, from silent film intertitles to modern AI-driven localization, this introduction to the special issue identifies precedents of adaptive practices and professional resilience. The transition from silent film to sound, which necessitated new workflows (dubbing/subtitling), is presented as a crucial historical analogue for interpreting the current AI upheaval. This analysis demonstrates that technological shifts invariably force the creation of new professional avenues and skills. The papers in this collection investigate the dynamic interplay between technology, evolving audience consumption (e.g., "Netflixication") and the expanding scope of AVT, particularly in accessibility modalities (audio description and SDH). The ultimate objective is to provide a nuanced perspective on how AVT can not only survive but also adapt and redefine the human factor within this rapidly evolving global media ecosystem, positioning the field at a critical juncture between automation and professional expertise.